Pemantapan Strategi Pemasaran Pada Pelaku UMKM di Kecamatan Sidayu Kabupaten Gresik - Ismiyah, Elly; Widyaningrum, Dzakiyah (JURNAL PENGABDIAN MANAJEMEN, 2022)
Sidayu is a sub-district in the Gresik district which is located on the north coast of the island of Java. Its strategic location makes the potential for entrepreneurship even greater. Many micro, small and medium enterprises (MSMEs) are growing, ranging from food, beverages, crafts, to clothing. In order to protect the MSME actors, the Sidayu MSME Association was established, which is abbreviated as ASUMSI. Many trainings have been provided to support the smooth running of ASUMSI members' businesses, one of which is training on marketing. However, based on the results of interviews with several members of ASUMSI, it was found that there are still many businesses that are underdeveloped, mainly due to limitations in marketing products which are only limited to local areas. The purpose of this service activity is to provide stabilization for MSMEs in Sidayu District regarding what marketing strategies should be taken so that the business that is run can continue and develop. The activity was carried out at the Polindes Telaga Rambit Village, Purwodadi, Sidayu, on March 20, 2022 attended by ASUMSI members. The method used is counceling. During their activities, business actors are given exposure to material related to the STP (Segmentation, Targeting, and Positioning) concept, then assisted to conduct an analysis of Strength, Weakness, Opportunity and Threat (SWOT) in determining marketing strategy by incorporating the concept of the 4P strategy mix mix (Product, Price, Place, and Promotion). The results of this activity can be seen directly in the discussion session that participants feel they have learned new knowledge that is ready to be applied after returning from the event